Long-term mental wellbeing and functioning after surgery for cauda equina syndrome. - James E Hazelwood (Public Library of Science (PLoS), 2021)
Introduction Cauda Equina Syndrome (CES) can cause persisting life-changing dysfunction. There is scarce literature regarding the long-term assessment of CES symptoms, and rarer still is the impact of these symptoms on mental wellbeing investigated. This study assessed the long-term patient reported mental wellbeing outcomes of post-operative CES patients. Methods Patients who underwent surgery for CES between August 2013 and November 2014 were identified using an ethically approved database. They then completed validated questionnaires over the telephone assessing their mental and physical functioning (Short-Form 12 Questionnaire), generating the Physical Component Summary (PCS) and Mental Component Summary (MCS). Bladder, bowel and sexual function were also assessed using validated questionnaires. MCS scores were compared to both the Scottish mean and previously published cut-offs indicating patients at risk of depression. Correlations of MCS with bladder, bowel, sexual and physical dysfunction were examined and multifactorial regression to predict MCS from these variables analysed. Independent t-tests assessed the mean difference in MCS between patients presenting with incomplete CES (CES-I) and CES with retention (CES-R) and between those with radiologically confirmed and impending CES. Results Forty-six participants with a mean follow-up time of 43 months completed the study. The mean (±SD) MCS was 49 (±11.8) with 22% demonstrating poor mental health related quality of life in comparison to the Scottish mean. Overall, 37% had scores consistent with being at risk for depression with in the last 30 days, and 45% within the last 12 months. MCS was significantly correlated with Urinary Symptoms Profile (USP) score (-0.608), NBDS score (-0.556), ASEX score (-0.349) and PCS score (0.413) with worse bladder, bowel, sexual and physical dysfunction associated with worse MCS score. Multifactorial regression analysis demonstrated both urinary (USP score p = 0.031) and bowel function (NBDS score p = 0.009) to be significant predictive variables of mental health related quality of life. There were no significant mean differences in MCS between those presenting with CES-I and CES-R or those with radiologically complete and impending CES. Discussion This study demonstrates a high frequency of being at risk for depression in patients with CES and identifies outcome measures (physical, sexual and more so bladder and bowel dysfunction) associated with poorer mental wellbeing. Our large cohort and long follow-up highlight that CES patients should be considered at risk of depression, and the need to consider mental health outcomes following CES surgery.